2019
DOI: 10.1093/icb/icz002
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Smooth Muscle in Vertebrates: A Comparative Review of Structure and Function

Abstract: Although the airways of vertebrates are diverse in shape, complexity, and function, they all contain visceral smooth muscle. The morphology, function, and innervation of this tissue in airways is reviewed in actinopterygians, lungfish, amphibians, non-avian reptiles, birds, and mammals. Smooth muscle was likely involved in tension regulation ancestrally, and may serve to assist lung emptying in fishes and aquatic amphibians, as well as maintain internal lung structure. In certain non-avian reptiles and anurans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 127 publications
1
16
0
Order By: Relevance
“…These are only two of the many roles proposed for the contractile function of the ASM [100,102,103]. In a review published by CIERI [107], it has been suggested that ASM in the terminal bronchiole of mammals plays an important role in keeping the alveoli inflated at low lung volumes and that ASM might attenuate ventilation-perfusion heterogeneity by constricting airways in either the apex or base in different situations. Furthermore, the ASM is assigned an important role in the production of cytokines, chemokines, growth factors and ECM components [108].…”
Section: Asmmentioning
confidence: 99%
“…These are only two of the many roles proposed for the contractile function of the ASM [100,102,103]. In a review published by CIERI [107], it has been suggested that ASM in the terminal bronchiole of mammals plays an important role in keeping the alveoli inflated at low lung volumes and that ASM might attenuate ventilation-perfusion heterogeneity by constricting airways in either the apex or base in different situations. Furthermore, the ASM is assigned an important role in the production of cytokines, chemokines, growth factors and ECM components [108].…”
Section: Asmmentioning
confidence: 99%
“…Air is actively forced into the primitive lungs by muscles in the upper airways while emptying is also an active process driven by largely the smooth muscle of the lower airway (159)(160)(161)(162)(163)(164). Of note, much of the control mechanisms via the vagus nerve appears to have been established at the very earliest stages in the evolution of the lung and air breathing, while surfactants also date back to the earliest lungs and swim bladders (165)(166)(167)(168)(169)(170)(171). The evolution of the diaphragm, present only in mammals, and a separate relatively rigid thoracic cavity, together with robust elastic recoil provided for a much more efficient means of filling and emptying the lungs (dinosaurs, birds, and reptiles developed completely different mechanisms for filling and emptying their lungs).…”
Section: What Is the Role Of Asm If Any In Healthy Airways?mentioning
confidence: 99%
“…Emptying alveoli helps to both protect these fragile structures from barotrauma and prevent nitrogen narcosis. Surfactants appear to help unstick the closed alveoli, a role they probably served in the earliest rudimentary lungs (165,166).…”
Section: What Is the Role Of Asm If Any In Healthy Airways?mentioning
confidence: 99%
See 2 more Smart Citations